Ischemic stroke with extensive vasculopathy in a patient with neurofibromatosis type 1 - Fiona J. Desmond, MB BCh, BAO; Alina Buture, MD, PhD; Eoin C. Kavanagh, FFR, RCSI; Sean Murphy, MD, FRCPI (Radiology Case Reports, 2022)
Neurofibromatosis type 1 is an autosomal dominant genetic disorder with multisystem manifestations including vascular abnormalities. The condition is also associated with an increased risk of both ischemic and hemorrhagic stroke. Here we report a case of a 60-year-old male with known neurofibromatosis who presented with right sided hemiparesis. Neuroimaging work-up revealed left internal carotid artery dissection and tandem occlusion of the left internal carotid artery and left middle cerebral artery. There was associated territorial ischemic infarction. The patient was found to have extensive intra and extra cranial vasculopathy including gross basilar dolichoectasia and a right-sided cervical internal carotid artery pseudoaneurysm. This case highlights the clinical significance of neurofibromatosis associated vasculopathy which can result in stroke.